Gay love in two Argentinean soap operas. Between the reproduction of and the opposition to heteronormativity - Marentes, Maximiliano (2017)
In this paper, we analyzed two gay love stories that had a leading role in two recent Argentinean soap operas, Farsantes and Viudas e hijos del Rock & Roll. We propose three analysis axes to think about how these stories reproduce and contest heteronormativity: talking about sex, the happy ending and the intersection between sexual orientation and social class. The aim is to read these stories not only in the gender matrix to which of each one belongs to, but also in their relationship with a specific narrative memory typical of stories about homosexuality.